Analyisis of the hypsometric properties of the (Tle) Basin - Faraj, Darya Jamal Hama; Mohammed, P. D. Khalil Karim (Sulaimani Journal for Humanities, 2026)
Abstract The primary objective of this study is to analyze the hypsometric properties of the Tle Valley basin and to determine the geomorphological stage of the cycle of erosion that the basin has undergone. This involves comparing the values of these properties with those of four secondary sub-basins. To achieve the study's objectives, an inductive method and statistical analysis were employed, utilizing the analysis of a Digital Elevation Model (DEM 12.5m) and Geographic Information Systems (ArcGIS 10.8.2) within the study area.The significance of this research lies in identifying the geomorphological development stages and the erosion cycle of the Tle Valley basin to implement necessary soil and water conservation measures for the sustainable development of the region. Structurally, the study consists of an introduction and three main sections covering the natural environmental characteristics of the basin, the Hypsometric Curve (Hc), and the Hypsometric Integral (Hi).The study concludes that the shape of the Hypsometric Curve (Hc) for the main Tle Valley basin indicates that the basin has reached an advanced geomorphological stage, characterized by a distinct concavity in the curve. Furthermore, the Hypsometric Integral (Hi) value is (0.29), providing evidence that the basin has reached the "Old Age" (Monadnock) stage of the erosion cycle. Approximately (71%) of the basin's rock composition has been removed due to erosion and weathering processes, indicating that this portion has approached the base level, while (29%) of the rock composition remains. Conversely, three of the secondary sub-basins exhibit curves in the equilibrium stage, signifying the maturity stage of the geomorphological cycle, with Hypsometric Integral values ranging between (0.35) and (0.6).Based on the findings, the researcher recommends the construction of dams and water reservoirs on selected valleys for water storage and to limit soil erosion and land degradation. Additionally, the construction of small check dams on the Tle stream itself is suggested to prevent sediment accumulation, alongside utilizing its hydrological potential.
Keywords: Tle Valley Basin; Hypsometric Curve; Hypsometric Integral